Strategi Pengelolaan Media Sosial Instagram Oleh Humas Perumda Tirta Pakuan Sebagai Sarana Penyampaian Informasi Pelayanan - Deswita Zahra Andriani; Leonard Dharmawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the Instagram management strategy implemented by the Public Relations division of Perumda Tirta Pakuan in delivering public service information, driven by the need for fast, transparent, and interactive information delivery in the digital era. This research employed a descriptive qualitative approach. The research subjects consisted of the Assistant Public Relations Manager, social media team, call center officers, and customers who followed the company’s Instagram account, with data collection techniques including observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data validity was obtained through source and technique triangulation. The findings show that the Instagram management strategy has been implemented through stages of identifying public information needs, content planning, digital communication execution, and program evaluation; however, it has not been optimal due to delays in internal information flow, limitations in managing digital responses, and uneven information reach. The Instagram management strategy plays a role in supporting public service information delivery but requires stronger internal coordination and optimization of two-way communication.